Effectiveness of moxibustion for allergic rhinitis: protocol for a systematic review. Issue 5 (19th May 2015) - Chen, Sheng; Guo, Shengnan; Wang, Jun; Ha, Eunhae; Marmori, Federico; Wang, Yanping; Zhao, Jiping
Abstract : Introduction: The objective of this review is to systematically evaluate the effectiveness of moxibustion for treating allergic rhinitis (AR). Methods and analysis: The following databases will be searched from their inception to January 2015: MEDLINE, EMBASE, CINAHL, AMED, Web of Science, Ovid Healthstar, PubMed, SciELO, the China National Knowledge Infrastructure Database, the Chongqing VIP Chinese Science and Technology Periodical Database, the Chinese Biomedical Database, the Wanfang Database, the Japanese Medical Research Database, and Korean Medical Databases. The methodological quality will be assessed using the Cochrane risk of bias tool. The primary outcome is total nasal symptoms, which may be evaluated by any appropriate scores or other forms of measurement. Secondary outcome measures will include quality of life, total non-nasal symptoms, use of daily medication and laboratory indicators. Ethics and dissemination: Because this study will not involve patients, institutional review body permission is not required. The systematic review will be published in a peer-reviewed journal. The review will also be disseminated electronically and in print to help guide healthcare practice and policy. Trial registration number: PROSPERO CRD42014013275.